IITA and NAQS strengthen partnership for safer germplasm xechange and plant health biosecurity - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2025)
In a significant step toward strengthening Nigeria’s agricultural biosecurity, IITA–CGIAR Germplasm Health Unit (GHU) hosted the Comptroller General (CG) of the Nigeria Agricultural Quarantine Services (NAQS), Dr Vincent Isegbe alongside other officials of NAQS in a strategic workshop held from 27–29 October.